2007
DOI: 10.1186/ar2152
|View full text |Cite
|
Sign up to set email alerts
|

Replication of the genetic effects of IFN regulatory factor 5 (IRF5) on systemic lupus erythematosus in a Korean population

Abstract: Recently, two studies provided convincing evidence that IFN regulatory factor 5 (IRF5) gene polymorphisms are significantly associated with systemic lupus erythematosus (SLE) in several white populations. To replicate the association with SLE in an Asian population, we examined the genetic effects in our SLE cohort from a Korean population. A total of 1,565 subjects, composed of 593 cases and 972 controls, were genotyped using the TaqMan® (Applied Biosystems, Foster City, CA, USA) method. The genetic effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
51
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 10 publications
4
51
0
Order By: Relevance
“…18 Since then, several additional studies have evaluated the association between IRF5 and SLE in Caucasian, [12][13][14]17,19 Korean 16 and Hispanic (Mexican) 15 populations, emphasizing the importance of this gene in SLE etiology. However, no studies have been reported to date in African Americans.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…18 Since then, several additional studies have evaluated the association between IRF5 and SLE in Caucasian, [12][13][14]17,19 Korean 16 and Hispanic (Mexican) 15 populations, emphasizing the importance of this gene in SLE etiology. However, no studies have been reported to date in African Americans.…”
Section: Discussionmentioning
confidence: 99%
“…9 Interferon regulatory factor-5 (IRF5), a transcription factor, regulates the expression of IFN-a genes, 10,11 thus making it a good candidate gene for SLE susceptibility. Recent publications have reported a significant association between single nucleotide polymorphisms (SNPs) and haplotypes of IRF5 and SLE, both in familyand population-based studies of patients from multiple ethnicities [12][13][14][15][16][17][18][19][20][21] (including meta-analyses) 16 ; however, these studies have not examined African Americans.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the meta-analysis of rs2004640, our data on Japanese subjects and previously published data on Korean subjects (14) were pooled using the DerSimonian-Laird method with the random effects model (22). Lack of heterogeneity between the 2 populations was examined using the Breslow-Day test of homogeneity.…”
Section: Methodsmentioning
confidence: 99%
“…Thus far, only 1 study of IRF5 polymorphisms in Asian populations has been published (14). In that examination of 4 SNPs, only 1 of them corresponded to the SNPs that define the Caucasian risk haplotype (14).…”
mentioning
confidence: 99%